Syariah Provisions On Financial Markets - Rahmatul Dini; Savira Sinaga Savira Sinaga; Nomi Prastiwi (Proceeding International Seminar of Islamic Studies, 2019)
This article discusses the understanding, history of Islamic financial markets, functions and characteristics of Islamic finance, financial market products and characteristics of Islamic and conventional financial markets. The development of the Islamic economy in Indonesia is currently very rapid. Muslim societies are familiar with the practices of economic life based on conventional economic concepts not understanding the difference between conventional and sharia financial operations. This lack of understanding results in many who assume that there is no difference between the two. Therefore this article was made to discuss, and explore the provisions of Islamic financial markets that many do not understand, especially among the public. So the money market is a place of short-term money trading with a time not to exceed 360 days. The language of easy money markets is a place for selling money (Money Market). actors in the money market are banks, foundations, pension funds, insurance companies, large companies, government institutions, other financial institutions, community individuals.